Coloniality in the German Higher Education System: Implications for Policy and Institutional Practice - Lisa Unangst; Ana M. Martínez Alemán (Social Inclusion, 2021)
This article focuses on the public German higher education sector as a site upon and through which coloniality is enacted. This status quo indicates exclusionary effects and merits interrogation. We briefly discuss the history of German colonialism to understand how coloniality pervades higher educational structures in the German context today. Two proposals addressing coloniality in German higher education are made: the development of structures centering diverse faculty and the support of ethnic and identity studies.